Resource Efficiency in TPU: Implementation of English Language E-courses; Procedia - Social and Behavioral Sciences; Vol. 215 : International Education and Cross-Cultural Communication, Problems and Solutions, (IECC 2015) - Bolsunovskaya L. M. Ludmila Mihailovna; Chris Phillips; Kolbysheva Yu. V. Yuliya Vladimirovna; Rymanova I. E. Irina Evgenievna; Strelnikova A. B. Anna Borisovna (2015, 2015)
Title screen